Pemeliharaan Anak Yatim dalam Perspektif Al-Qur’an Analisis Asbabun Nuzul Q.S Al-Baqarah Ayat 220 (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study examines the asbab al-nuzul of Q.S. al-Baqarah (2):220 and its relevance to the concept of orphan care in Islamic thought. Employing a library research method with a qualitative-descriptive approach, the study analyzes the Qur’anic text, classical tafsir works (such as al-Tabari, Ibn Kathir, and al-Qurtubi), authoritative asbab al-nuzul sources (al-Waḥidi and al-Suyuti), as well as contemporary scholarly literature and recent journal articles (2020–2024). The findings indicate that Q.S. al-Baqarah (2):220 was revealed as a corrective response to the excessive caution among the Companions following stern warnings against unjust consumption of orphans’ property. The verse emphasizes the principle of islaḥ (reform and welfare) as the primary criterion for interactions with orphans. A thematic reading, complemented by related verses such as Q.S. al-Nisa’ (4):2 and (4):10 and Q.S. al-Duha (93):9, demonstrates that orphan care in Islam integrates legal, ethical, psychological, and social dimensions, prioritizing dignity and social integration over isolation. Contemporary studies further affirm the relevance of this verse to modern child protection principles, particularly the best interest of the child and family-based care models. This study recommends the development of orphan care policies rooted in family and community-based approaches, guided by trustworthiness, transparency, and holistic welfare.